Effects of early marriage among women married before reaching 18 years old (qualitative study approach) - Gelchu Adola, Shiferaw; Wirtu, Dessalegn (Frontiers in Sociology, 2024)
BackgroundThe consequences of early marriage have become a global concern for young women. The detrimental effects of early marriage disproportionately affect girls. Regarding its effects in poor nations like Ethiopia, there is a dearth of data. As a result, this study offers baseline, first-hand, and updated information for both the nation and the study area.ObjectiveThe purpose of this study was to investigate the effects of early marriage on Guji women who were married before the age of 18.MethodsThis qualitative study used a phenomenological approach and was carried out from January to April 2024. An in-depth interview technique was employed to collect the data. The interviews were conducted in the Oromo language. A purposive sampling technique was applied to choose the study participants. A total of 25 women who met the eligibility criteria were selected. A thematic data analysis approach was employed to analyze the data in this study.ResultsThree themes, 10 subthemes, and more than hundreds of codes were extracted after the interview data were analyzed. The main themes and subthemes of this study were as follows: 1-Precipitators of early marriage (abduction and arranged marriage); 2-Consequences of early marriage (emotional damage, moral damage, early marriage is a risk factor for maternal and child health, early marriage is a major cause for girls to drop out of school, poverty, gender-based violence and divorce, lack of essential life skills); and 3-Attitudes toward early marriage (early marriage is a harmful cultural practice; girls should be protected).ConclusionThe study’s findings illustrated the multidimensional effect of early marriage, necessitating the involvement of numerous sectors and stakeholders. The community, religious leaders, the health, education, and legal sectors, as well as the parents of young girls, should all take an active role in delaying early marriage. This indicates the development of policies that permit cooperation amongst all relevant parties. Creating awareness among girls, families, and the community through community-based education is crucial. Early married women should participate in intervention programs to provide their experience to young girls. Women who are victims of early marriage must receive full support to mitigate its negative consequences.